The Effect of Moringa Leaf Juice, Lemon and Honey Intervention on Breast Milk Production Volume in Postpartum Mothers: An Experimental Study Based on Education Level in Kalisat District - Umi Kulsum, Trisiyawati; Anik Sri, Purwanti (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2025)
maternal education greatly influences knowledge about breastfeeding, nutritional compliance, and the success of the intervention, the combination of moringa leaves, lemon, and honey can increase breast milk volume in postpartum mothers, This study aims to explore the effects of a combination of moringa leaf juice, lemon, and honey on breast milk volume in postpartum mothers, the research design uses quasi-experimental, to evaluate the effectiveness of giving moringa leaf juice, lemon, and honey on breast milk production volume. The study population was 100 postpartum mothers on days 2 to 10, Data analysis used the Paired t-test to compare changes in groups, and the Independent t-test and two-way ANOVA to compare between groups and test interactions with education level, an increase in breast milk volume from pretest to posttest with varying magnitudes. Participants with higher education in the intervention group (ID 1, 3, and 4) experienced an increase of 31.8 ml, 27.3 ml, and 32.6 ml, secondary education (ID 5) showed a more substantial increase of 30.1 ml, education level as a covariate factor did not show a significant effect on the measured outcome (F = 1.17, p = 0.315), the interaction effect between group and education level (F = 0.22, p = 0.805). The absence of statistical significance in the education factor indicates that variations in educational background do not contribute meaningfully to variability, The results of the study showed that providing intervention in the form of moringa leaf juice combined with lemon and honey was able to significantly increase the volume of breast milk production in postpartum mothers